The Influence of Capital, Risk Knowledge, Digital Literacy, Sharia Financial Literacy on Entrepreneurial Interest in Uin North Sumatra Students - Syafriani, Annisa; Sri Ramadhani; Qarni, Waizul (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to determine and analyze capital, risk knowledge, digital literacy, and Islamic financial literacy, on entrepreneurial interest in UIN North Sumatra students. This research approach uses quantitative research. The data used in this study are primary data obtained from questionnaires. While the data analysis method in this study uses multiple linear regression using SPSS software version 25. The sample of this study were students from all Departments of the 2021 Class of the State Islamic University of North Sumatra (UINSU) totaling 100 respondents. The results of the study showed that the influence of the capital variable (X1) had a positive and significant effect on entrepreneurial interest (Y) in UIN North Sumatra students, with the results of the t-regression test that the probability sig value for the influence of X1 on Y was 0.000 < 0.05 and t count 5.936 < t table 1.960. The influence of the risk knowledge variable (X2) does not have a positive and insignificant effect on entrepreneurial interest (Y) in UIN North Sumatra students, with the results of the t-regression test with a probability sig value for the influence of X2 on Y of 0.315 > 0.05 and t count 1.011 < t table 1.960. The influence of the digital literacy variable (X3) has a positive and significant effect on entrepreneurial interest (Y) in UIN North Sumatra students, with the results of the t-regression test with a probability sig value for the influence of X3 on Y of 0.003 < 0.05 and t count 3.011 > t table 1.960. The influence of the Islamic financial literacy variable (X4) does not have a positive and insignificant effect on entrepreneurial interest (Y) in UIN North Sumatra students, with the results of the t-regression test with a probability sig value for the influence of X4 on Y of 0.098 > 0.05 and t count 1.670 < t table 1.960. While simultaneously the influence of capital (X1), risk knowledge (X2), digital literacy (X3), and Islamic financial literacy (X4) on entrepreneurial interest (Y) in UIN North Sumatra students has a significant effect together on the entrepreneurial interest (Y) of UIN North Sumatra students with an F count value of 13,436 > F table 3.25. while the significance value of the probability F count is 0.000 < 0.05.